Impact of chronic GLP-1 receptor agonist and SGLT-2 inhibitor therapy on in-hospital outcomes of patients with diabetes mellitus hospitalized with acute myocardial infarction. (3rd October 2022) - Trombara, F; Cosentino, N; Genovese, S; Bonomi, A; Ludergnani, M; Poggio, P; Agostoni, P G; Marenzi, G
Abstract: Background: Glucagon-like peptide-1 receptor agonists (GLP-1 RA) and sodium glucose cotransporter-2 inhibitors (SGLT-2i) demonstrated cardiovascular and renal protection in addition to their glucose-lowering effect. Whether their benefits occur also in patients with diabetes mellitus (DM) during hospitalisation with acute myocardial infarction (AMI) has not been investigated yet. Purpose: We evaluated in-hospital outcomes of patients hospitalised with AMI according to their chronic use (before hospitalisation) of GLP-1 RA and SGLT-2i therapy. Methods: Using administrative healthcare databases, we analysed patients hospitalised with a primary diagnosis of AMI from 2010 to 2019 in the Lombardy region, Italy. Patients were stratified according to their DM status, then divided into three cohorts: Group 1 (non-DM patients); Group 2 (DM patients taking GLP-1 RA or SGLT-2i); and Group 3 (DM patients not taking GLP-1 RA and/or SGLT-2i). Patients were matched in a 1:1:1 ratio using a propensity score including all available variables. The primary endpoint of the study was the composite of in-hospital mortality, acute heart failure, and acute kidney injury requiring renal replacement therapy. Results: We identified 146, 800 patients hospitalised with AMI (26% of them with DM). After propensity score matching, 1, 030 patients were included in each group. The primary endpoint rate in the overall population was 16% (n=502) and it significantly increased going from Group 1 to Group 3 (13%, 16%, and 20% respectively; p for trend <0.0001). The risk of the composite endpoint significantly increased from Group 1 to Group 3 (P for trend <0.0001). In comparison with Group 2, Group 3 had a significant higher risk of the composite endpoint (OR 1.40 [95% CI 1.11–1.77]). Conclusions: Our study shows that DM patients hospitalised with AMI and on chronic GLP-1 RA and/or SGLT-2i therapy have a better in-hospital clinical outcome than DM patients without them. Funding Acknowledgement: Type of funding sources: None.